West African agriculture and climate change: A comprehensive analysis - Togo - Tchinguilou, Abiziou; Jalloh, Abdulai; Thomas, Timothy S. (International Food Policy Research Institute, 2012)
This summary note is an excerpt from the chapter on Togo that will appear in the peer-reviewed IFPRI monograph, West African Agriculture and Climate Change: A Comprehensive Analysis.